2017
DOI: 10.3171/2015.12.jns152461
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcomes after stereotactic radiosurgery for the treatment of cerebral arteriovenous malformations

Abstract: OBJECTIVE Patients with cerebral arteriovenous malformations (AVMs) commonly present with seizure. Seizure outcomes in patients treated with stereotactic radiosurgery (SRS) are poorly defined. A case series of patients with cerebral AVMs treated with SRS is presented to evaluate long-term seizure outcome. METHODS A retrospective review of the medical record was performed, identifying 204 consecutive patients with AVMs treated with SRS between January 1991 and June 2012. Clinical and radiographic data were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…However, two studies published after the one by Chen et al 4 that included 151 total patients demonstrated that AVM obliteration does not necessarily predict seizure outcomes. 7,30 In our study, we observed that seizure remission was not significantly associated with AVM obliteration, suggesting that SRS provides at least some seizure control via radiation to the surrounding tissue. 4,12,15 Although not well understood, it has been suggested that perinidal radiation provides seizure relief through multiple mechanisms, including inhibition of protein synthesis, neuromodulatory effects on local inhibitory and excitatory neurons, perinidal gliotic capsule formation, dendritic sprouting, and cortical reorganization.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, two studies published after the one by Chen et al 4 that included 151 total patients demonstrated that AVM obliteration does not necessarily predict seizure outcomes. 7,30 In our study, we observed that seizure remission was not significantly associated with AVM obliteration, suggesting that SRS provides at least some seizure control via radiation to the surrounding tissue. 4,12,15 Although not well understood, it has been suggested that perinidal radiation provides seizure relief through multiple mechanisms, including inhibition of protein synthesis, neuromodulatory effects on local inhibitory and excitatory neurons, perinidal gliotic capsule formation, dendritic sprouting, and cortical reorganization.…”
Section: Discussionmentioning
confidence: 55%
“…Of note, our results indicate that the proportion of patients reaching freedom from maintenance AED therapy (18%) was lower than that reported in previous studies. 7,30,39 In general, our approach has been to attempt to wean patients off AEDs after 2 years of seizure freedom. 4 Nonetheless, we found that many patients were maintained on 1 AED despite AVM obliteration and seizure freedom for > 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the inherent difficulty of achieving a complete obliteration for such challenging lesions, seizure control and prevention of neurological deficit progression are key objectives in the radiosurgical treatment of large AVMs. The dramatic positive effect of radiosurgical treatment on seizure outcome has been previously reported to be up to 80% 4,7,24,33 and related to obliteration. This also holds true for large cerebral AVMs, as we reported 50% of patients to be seizure-free (Engel Class I) and 25% to have a significant reduction in epileptic episodes (Engel Class II), thereby achieving an overall good outcome in seizure control for 75%.…”
Section: Discussionmentioning
confidence: 92%
“…Radiosurgery for arteriovenous malformations may give excellent outcomes for associated epilepsy and positive prognostic factors have been reported to be presentation with haemorrhage rather than epilepsy and the absence of post-treatment haemorrhage [163–165]. A recent meta-analysis of stereotactic radiosurgery for mesial temporal sclerosis [166] showed that the total number of patients reported remains low (<200) but that half became seizure free at a median of 14 months after treatment with a complication rate of around 8% (excluding headache which was more common) and rates of visual field defects similar to open surgery.…”
Section: Epilepsy Surgerymentioning
confidence: 99%